THE LONG-TERM EFFECTS OF HEDGE FUND ACTIVISM - Bebchuk, Lucian A.; Brav, Alon; Jiang, Wei (Columbia law review, 2015)
We test the empirical validity of a claim that has been playing a central role in debates on corporate governance—the claim that interventions by adivist hedge funds have a detrimental effect on the long-term interests of companies and their shareholders. We subject this claim to a comprehensive empirical investigation, examining a longfive-year window following activist interventions, and we find that the claim is not supported by the data. We find no evidence that activist interventions, including the investment-limiting and adversarial interventions that are most resisted and criticized, are followed by short-term gains in performance that come at the expense of long-term performance. We also find no evidence that the initial positive stock-price spike accompanying activist interventions tends to be followed by negative abnormal returns in the long term; to the contrary, the evidence is consistent with the initial spike reflecting correctly the intervention's long-term consequences. Similarly, we find no evidence for pump-and-dump patterns in which the exit of an activist is followed by abnormal long-term negative returns. Our findings have significant implications for ongoing policy debates.Policymakers and institutional investors should not accept the validity of the assertions that activist interventions are costly to firms and their shareholders in the long term; such claims do not provide a valid basis for limiting the rights, powers, and involvement of shareholders.